2008
DOI: 10.1007/s10800-008-9569-4
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical promotion of deep oxidation of methane on Pd/YSZ

Abstract: Electrochemical catalysts based on Pd deposited by Physical Vapour Deposition on YSZ were used for methane deep oxidation. Different thicknesses of Pd films varying from 11 to 75 nm were catalytically characterized between 150 and 750°C. The Pd loadings were extremely low. Catalytic and EPOC experiments were carried out on those electrochemical catalysts. Their catalytic activities were compared with the performances of a reference catalyst. It was found that the catalytic activity can be in situ tuned by appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…Conse- quently, the catalytic reaction rate was increased by anodic polarisation, exhibiting electrophobic behaviour [8]. This result totally agrees with other electrochemical promotion studies on methane combustion, reported by Giannikos et al [17] and Roche et al [34]. These authors also observed electrophobic behaviour under oxidising conditions over palladium catalysts prepared by paste and sputtering, respectively.…”
Section: Original Research Papersupporting
confidence: 87%
See 2 more Smart Citations
“…Conse- quently, the catalytic reaction rate was increased by anodic polarisation, exhibiting electrophobic behaviour [8]. This result totally agrees with other electrochemical promotion studies on methane combustion, reported by Giannikos et al [17] and Roche et al [34]. These authors also observed electrophobic behaviour under oxidising conditions over palladium catalysts prepared by paste and sputtering, respectively.…”
Section: Original Research Papersupporting
confidence: 87%
“…As shown in Figure 8, the rate enhancement ratio was of 5.6. The Faradaic efficiency value was found to be 764 (the highest value reported for the electrochemical promotion of this reaction [17,[33][34][35]). This difference could be explained by the role of ceria film.…”
Section: Original Research Papermentioning
confidence: 99%
See 1 more Smart Citation
“…conductivity are also under investigation. Methane oxidation was studied by Roche et al [38] using Pd on YSZ prepared by physical vapour deposition (PVD) where under positive polarization Faradaic efficiencies up to 258 and rate enhancement ratios up to 50 were observed. Propene oxidation is another reaction studied using various working electrodes deposited on several solid electrolytes.…”
Section: Electrochemical Promotion Of Reactions With Environmental Anmentioning
confidence: 99%
“…It is also worth noting that heat-transfer and mass transfer limitations are coupled directly via the Lewis number [16] and thus, in the absence of mass-transfer limitations (which is a necessary condition for obtaining large L and 1 values, [2,3,[17][18][19][20] for example, L as high as 3 10 5[2-5, 17-20] and 1 as high as 1400, [17,18] as reported by many authors in the literature for extremely fuel-lean conditions), [2][3][4][16][17][18][19] there should be no concern about heat-transfer limitations and concomitant catalysttemperature increases. Thus, the first issue which must be ad-dressed in any EPOC study-and in any catalytic study in general-is the absence of mass-transfer limitations.…”
mentioning
confidence: 99%